Readiness of Small Medium Enterprises in West Sumatra Faces ASEAN Economic Community - Masdupi, Erni; Rahmiati, Rahmiati; Firman, Firman (Jurnal Kajian Manajemen Bisnis, 2015)
One era that will be faced by SMEs and economic actors is ASEAN Economic Community (AEC) in 2015. The problem is that SMEs in West Sumatra have to contend with the economic actors who come from other ASEAN member countries relatively more developed and stronger in terms of capital, technology, human resources and other resources. Without any serious effort from all parties, the Indonesian economic actors (such as SMEs in West Sumatra) will be spectators in their own country. Therefore, we need to do research to analyze the readiness of SMEs in West Sumatra to face AEC in 2015 and found the empowerment model to support the competitiveness of SMEs in the region. The population was food-producing SMEs in the city of Bukittinggi and Padang with snowball sampling techniques. Data analysis techniques are quantitative descriptive analysis.